2007
DOI: 10.1158/1078-0432.ccr-07-0071
|View full text |Cite
|
Sign up to set email alerts
|

De novo Identification of MIZ-1 (ZBTB17) Encoding a MYC-Interacting Zinc-Finger Protein as a New Favorable Neuroblastoma Gene

Abstract: Purpose: Neuroblastoma is a childhood cancer that exhibits either a favorable or an unfavorable phenotype. Favorable neuroblastoma genes (EPHB6, EFNB2, EFNB3, NTRK1, and CD44) are genes whose high-level expression predicts favorable neuroblastoma disease outcome. Accordingly, the forced expression of these genes or their reactivation by gene silencing inhibitors in unfavorable neuroblastoma cells results in suppression of tumor growth and metastases. This study was undertaken to design an experimental strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…We have previously reported that known favorable neuroblastoma genes are epigenetically silenced in unfavorable neuroblastoma cells (13). In addition, our study suggests that favorable neuroblastoma gene expressions can be considered molecular indicators of the effectiveness of chemotherapeutic agents against neuroblastoma cells (9).…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…We have previously reported that known favorable neuroblastoma genes are epigenetically silenced in unfavorable neuroblastoma cells (13). In addition, our study suggests that favorable neuroblastoma gene expressions can be considered molecular indicators of the effectiveness of chemotherapeutic agents against neuroblastoma cells (9).…”
Section: Introductionmentioning
confidence: 55%
“…Notably, MYCN-amplified neuroblastomas, the most aggressive form of the tumor, exhibit little or no expression of these genes. Thus far, several favorable neuroblastoma genes have been identified, which include EPHB6, EFNB2, EFNB3, NTRK1 (TrkA), CD44 and MIZ-1 (7)(8)(9)(10)(11)(12). We have previously reported that known favorable neuroblastoma genes are epigenetically silenced in unfavorable neuroblastoma cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, deletions of variable size and location within 1p36 are frequent in multiple human tumors, leading to the suggestion that the region contains several tumor suppressor genes (Bagchi and Mills 2008). One example is neuroblastoma and MIZ-1 has tumor-suppressor properties in this neoplasm (Ikegaki et al 2007). Mutations and SNPs close to the MIZ-1 gene have been associated with blindness and congenital heart failure.…”
Section: Human Tumorsmentioning
confidence: 99%
“…In fact, similar observations were previously made in genes residing in 1p36. These include ZBTB17 (MIZ-1) (29) and CHD5 (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…shares several characteristics with favorable neuroblastoma genes (EPHB6, EFNB2, EFNB3, TrkA, CD44 and MIZ-1) (22,23,29). Their expression is low in neuroblastoma cell lines and can be enhanced by gene silencing inhibitors.…”
Section: Epha2 Expression Is Not Associated With Neuroblastoma Diseasmentioning
confidence: 99%